The Influence of Financial attitude on Sharia Investment Intention among Generation Z in Surabaya: The Mediating Role of Financial literacy - Erry Arista Pratama; Fira Nurafini (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
This study aims to examine the influence of financial attitude on investment intention in the Islamic capital market among Generasi Z in Surabaya with financial literacy as a mediating variable. The research employs a quantitative approach using primary data collected through an online questionnaire distributed via Google Forms. The respondents consist of 153 Generasi Z individuals residing in Surabaya with diverse demographic backgrounds. The variables analyzed in this study include financial attitude as the independent variable, financial literacy as the mediating variable, and investment intention as the dependent variable. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique to test both direct and indirect relationships among variables. The results indicate that financial attitude has a significant positive effect on financial literacy. However, financial attitude does not have a significant direct effect on investment intention in the Islamic capital market. Meanwhile, financial literacy has a significant positive effect on investment intention and also functions as a mediating variable in the relationship between financial attitude and investment intention. These findings highlight the importance of financial literacy in transforming positive financial attitudes into stronger intentions to invest among Generasi Z.